2018
DOI: 10.31768/2312-8852.2018.40(1):2-9
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF COMPONENTS OF microRNA MACHINERY IN CARCINOGENESIS

Abstract: MicroRNAs (miRNAs) are a broad class of non-coding RNAs nearly 21 nucleotides length, which play crucial functions in posttranscriptional gene regulation. These molecules are associated with many developmental and cellular processes in eukaryotic organisms. Current investigation has reported major factors contributing to miRNA biogenesis and has constituted basic principles of miRNA function. More recently, it was confirmed that various miRNAs are clearly implicated in human malignancies, such as lung, breast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…In the human genome, miRNAs regulate protein encoding genes at a rate of approximately 1:3, controlling cell apoptosis, proliferation, differentiation, metabolism, individual development and tumorigenesis, and drug resistance. [14][15][16] Target gene expression is regulated by two mechanisms: (i) binding to the untranslated region (3'UTR) of the target messenger RNA (mRNA) 3' end, inhibiting its translation; and (ii) like small interfering RNA (siRNA), miRNA binds to the target and degrades target mRNA. [17][18][19] Recent studies have found that miRNAs regulate drug resistance by mediating their targeting genes in various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In the human genome, miRNAs regulate protein encoding genes at a rate of approximately 1:3, controlling cell apoptosis, proliferation, differentiation, metabolism, individual development and tumorigenesis, and drug resistance. [14][15][16] Target gene expression is regulated by two mechanisms: (i) binding to the untranslated region (3'UTR) of the target messenger RNA (mRNA) 3' end, inhibiting its translation; and (ii) like small interfering RNA (siRNA), miRNA binds to the target and degrades target mRNA. [17][18][19] Recent studies have found that miRNAs regulate drug resistance by mediating their targeting genes in various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Novel approaches in Rcc diagnosis and treatment are required. miRs have been reported to be involved in a number of biological processes of tumorigenesis (6), and miR replacement therapy has been considered to be promising in cancer treatment (14).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are a class of small non-coding RNAs that suppress gene expression by binding to the 3'-untranslated region of mRNA at the post-transcriptional level (5). Accumulating evidence suggested that miRs may be important in the development of malignancies (6). Previous studies demonstrated that miRs are involved in a number of cancer cell biological processes, including metastasis (7), invasion (8), angiogenesis (9), proliferation, apoptosis (10), differentiation (11), metabolism (12) and drug resistance (13).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not surprising that aberrant miRNA expression is involved in the pathogenesis of many diseases including cardiovascular diseases, neurodegenerative diseases, hematologic diseases, osteologic diseases and cancer. To this day, more than 2,650 different microRNAs have been described in various documents [2][3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the intracellular occurrence, micro-RNAs were also detected in the extracellular area -in the blood and its derivatives (plasma, serum), but also in the urine, saliva and other body fluids 5,6 . It has been proven that levels of circulating microRNAs are not random and reflect the events occurring within the organism/body.…”
Section: Introductionmentioning
confidence: 99%